2014
DOI: 10.3109/00016489.2013.851797
|View full text |Cite
|
Sign up to set email alerts
|

Mapping affected territory of anterior/posterior inferior cerebellar artery infarction using a vestibular test battery

Abstract: In the PICA group, 8 (36%) of 22 ears had a mean hearing level >25 dB. All six ears (100%) in the AICA group had abnormal hearing, and thus both groups revealed a significant difference. Conversely, significant differences were not observed in the vestibular test battery between the PICA and AICA groups. MRI demonstrated infarction at the brainstem for six patients, while one patient also had cerebellar involvement, indicated by loss of visual suppression on caloric nystagmus. Six patients showed infarction at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…(17) Conversely, significant differences were not observed in the vestibular test battery between the PICA and AICA stroke, where cVEMPs were abnormal in 50% of the PICA stroke patients and 66% of the AICA stroke patients. (22) The limitations of our study are retrospective data collection, the fact that all patients came from tertiary medical center and the relatively large number of patients with unexplained dizziness. Figure 1.…”
Section: Discussionmentioning
confidence: 98%
“…(17) Conversely, significant differences were not observed in the vestibular test battery between the PICA and AICA stroke, where cVEMPs were abnormal in 50% of the PICA stroke patients and 66% of the AICA stroke patients. (22) The limitations of our study are retrospective data collection, the fact that all patients came from tertiary medical center and the relatively large number of patients with unexplained dizziness. Figure 1.…”
Section: Discussionmentioning
confidence: 98%
“…Weng and Young found slightly higher rates of AC cVEMP and BC oVEMP abnormalities in AICA (66 and 100%) compared with PICA (50 and 86%) infarction. 137 Not Fig. 7 Air-conducted (AC) cervical vestibular-evoked myogenic potential (cVEMP) (0.1 ms click) and bone-conducted (BC) ocular vestibularevoked myogenic potential (oVEMP) (1 ms square wave pulse) recordings in patients with stroke.…”
Section: Strokementioning
confidence: 99%
“…surprisingly, studies have shown a correlation between the presence of hearing loss and vestibular test abnormalities, including VEMPs. 134,137,138 Oh et al described two patients with acute AICA infarction, both with unilateral hearing loss and absent oVEMPs in response to stimulation of the affected ear. 134 In another case of confirmed AICA infarction, patterns of audiovestibular test abnormalities followed the vascular distribution of the common cochlear artery, producing abnormal cVEMP, posterior canal vHIT, and hearing loss.…”
Section: Strokementioning
confidence: 99%